2013
DOI: 10.1002/cjoc.201300036
|View full text |Cite
|
Sign up to set email alerts
|

Copper Hydride‐Catalyzed Conjugate Reduction‐Aldol Addition Domino Reaction of α,β‐Unsaturated Carboxylates with Ketones

Abstract: Copper hydride-catalyzed conjugate reduction-intermolecular aldol addition domino reactions were realized using α,β-unsaturated carboxylates as hydride acceptors and a silane as the reducing reagent. High diastereoselectivities were achieved with 4,5-bis(diphenylphosphino)-9,9-dimethylxanthene as the ligand and tert-butyl acrylate as the hydride acceptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…23 Accordingly, we used substituted acetophenones to explore the generality of the current reaction and its selectivity. As shown in Table 2, good to excellent yields were obtained in all the cases.…”
mentioning
confidence: 99%
“…23 Accordingly, we used substituted acetophenones to explore the generality of the current reaction and its selectivity. As shown in Table 2, good to excellent yields were obtained in all the cases.…”
mentioning
confidence: 99%
“…Our previous results suggested that higher diastereoselectivity could be achieved with hindered acrylate in the copper hydride-catalyzed reductive aldolization of acetophenone [ 19 ]. Therefore, tert- butyl acrylate ( 1d ) was used to replace methyl acrylate, and several biphosphorous ligands were screened for improving the diastereoselectivity ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Copper-catalyzed reductive intermolecular aldolization reactions have been discussed previously [ 17 19 ]. Constantino has demonstrated that aldol reactions of enolates with ketones or aldehydes are much faster than the Claisen condensation [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…CuF(PPh 3 ) 3 ·2MeOH, with good solubility and high activity in catalyzing conjugate addition and the subsequent reaction [25,26,27], was employed to catalyze the reaction of 1 a , and a 72% yield of 2a was obtained. Interestingly, the cis - 2a isomer was the dominant one with a 61:39 cis -/ trans -ratio (entry 8).…”
Section: Resultsmentioning
confidence: 99%
“…Previous results indicated that using bulky alkyl α,β-unsaturated esters gave higher diastereoselectivity in reductive aldol domino reactions [26]. Accordingly, we resorted to bulky alkyl groups in the itaconate.…”
Section: Resultsmentioning
confidence: 99%